DYNAMICS OF CYTOKINES IN ORAL FLUID OF COMPLETELY EDENTULOUS PATIENTS AFTER PROSTHETIC REHABILITATION WITH IMPLANTS - V.A. Ponomarenko; Y.I. Sylenko; M.V. Khrebor (Український стоматологічний альманах)
One of the most difficult tasks in modern prosthetic dentistry is total rehabilitation of patients with dentition defects. The number of patients with removable dentures is growing due to the widespread dental diseases and progressive aging of the world population especially in industrialized countries, where life is increasing.